Preparation of Diamond/Ceramic Composite by Sol-Gel Method and Its Physical Properties - Gao, Kai; Li, Zhihong; Na, Li; Shan, Dongdong; Wang, Kaiyue; Zhu, Yumei (Asian Journal of Chemistry, 2012)
A diamond/ceramic composite was fabricated by sintering a composite precursor composed of a synthetic collosol and gelatine and thus the SiO2-Al2O3-B2O3-CaO-MgO-ZnO-K2O-Li2O ceramic phase was introduced into diamond powder. The gelatine powder was characterized with DSC, FTIR, SEM, EDS and XRD after thermal treatment. Results showed that the sol-gel method had dramatically reduced the softening temperature of the glass and the dose of the alkali metal added could be well-controlled. Meanwhile, the dielectric loss was ultimately reduced and the resistance and dielectric property of the sheet-shaped composite was calculated by means of a resonance circuit at high frequency. The results indicated that the resistance of diamond massive composite was slightly larger than that of diamond thin-film, while the dielectric loss of the former was less than 0.002 and lower than the latter.